The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1590/s1516-05722009000100013
|View full text |Cite
|
Sign up to set email alerts
|

Efeito antimicrobiano in vitro do extrato de jabuticaba [Myrciaria cauliflora (Mart.)O.Berg.] sobre Streptococcus da cavidade oral

Abstract: Este estudo avaliou a ação do extrato etanólico das folhas de Myrciaria cauliflora (Mart.)O.Berg. sobre três culturas de Streptococcus formadoras do biofilme dental. A atividade antimicrobiana foi determinada pelo método de difusão em meio sólido. Os dados obtidos foram satisfatórios para todas as espécies ensaiadas (Streptococcus mutans ATCC 25175, Streptococcus sobrinus ATCC 27609 e Streptococcus sanguis ATCC 10557) gerando halos de inibição quando utilizado o extrato puro e diluições 1:2 e 1:4. Os resultado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 15 publications
0
3
0
3
Order By: Relevance
“…The use of medicinal plants for the treatment of various diseases including bacterial and fungal infections is common in Brazil (Carvalho et al, 2009;Pereira et al, 2007;Schubert et al, 2007). Worldwide, many search groups that use plants detect secondary metabolites with antimicrobial properties in an attempt to find new antimycobacterial or antifungals compounds (Cos et al, 2006;Soberón et al, 2007;Rangasamy et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The use of medicinal plants for the treatment of various diseases including bacterial and fungal infections is common in Brazil (Carvalho et al, 2009;Pereira et al, 2007;Schubert et al, 2007). Worldwide, many search groups that use plants detect secondary metabolites with antimicrobial properties in an attempt to find new antimycobacterial or antifungals compounds (Cos et al, 2006;Soberón et al, 2007;Rangasamy et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…(Myrtaceae) is a native plant from Brazil and can be found throughout the country [135]. Tests performed in vitro using the alcoholic extract of this plant's leaves against S. mutans demonstrated that this extract acts on biofilm formation and could be an alternative for use in toothpastes [136,137].…”
Section: Myrciaria Cauliflora (Mart) O Bergmentioning
confidence: 99%
“…Myrciaria Cauliflora pertencente à família Myrtaceae, desempenha ações antiinflamatória, antiviral, hipolipidêmica, contribui na redução de doenças cardiovasculares e também antimicrobiana frente a Lactobacillus casei e Streptococcus mutans (CARVALHO et al, 2009). O objetivo do estudo foi desenvolver formulações de bala fitoterápica à base de os extratos da casca do fruto de Punica granatum Linn (romã) e de folhas de Myrciaria cauliflora (jabuticabeira) e avaliá-las quanto à atividade antibacteriana frente as bactérias cariogênicas.…”
Section: Introductionunclassified